Introduction to special Issue: future priorities in European media and communication research - Golding, Peter (2016)
(Excerto) The European Journal of Communication seeks to present the best in current research in the broad field of media and communication research. Irregularly, we seek to take stock by inviting a small group of leading scholars to present their work at a symposium on a common theme, which then forms the basis for a Special Issue of the Journal. In 2014, the European Science Foundation (ESF) published one of their ‘Forward Looks’ entitled Media in Europe: New Questions for Research and Policy. We subsequently invited several of the Forward Look’s authors to meet and discuss their work with us at a symposium hosted by the European University Cyprus, and the discussion and revised papers that resulted are published here.